EXPLORING SHARIA-BASED MSME DEVELOPMENT STRATEGIES THROUGH THE UTILIZATION OF MAJOO POINT OF SALE TECHNOLOGY - Nasir, Abdul; Rismaya, Erin (UIN Sunan Gunung Djati Bandung, 2024)
This study examines how Sharia economics integration in the MSME business model can be optimized using Majoo POS technology. In the era of globalization and rapidly developing information technology, Micro, Small, and Medium Enterprises (MSMEs) based on the Sharia economy need to continue to develop strategies to expand their markets and improve operational efficiency. MSMEs are the backbone of the national economy, but many face financial management and marketing challenges. The method used is a descriptive qualitative to identify the potential and challenges in implementing this strategy and provide recommendations for MSME actors and related stakeholders. The study results indicate that applying Sharia economics supported by Majoo POS technology can increase the competitiveness of MSMEs and positively contribute to the national economy. Majoo POS technology offers features that facilitate transaction recording, stock management, and real-time data analysis, which can improve the operational efficiency of MSMEs. The practical implications of this study are the importance of government and financial institution support in providing access and training related to technology for MSMEs based on the Sharia economy.